Aplikasi Reservasi Berbasis Web : Studi Kasus Dokter Psikolog - Dia Ragasari; Rama Satriana (Asosiasi Dosen Muda Indonesia, 2026)
Digital access to mental health services has become increasingly important as psychological consultation remains limited by time, cost, geographical barriers, and the availability of professional practitioners. This study aims to design and develop MindCare, a web-based reservation system that facilitates online appointment booking for psychological consultation services. The study employed the System Development Life Cycle (SDLC) method, consisting of planning, analysis, design, implementation, testing, deployment, and maintenance stages. The system was developed using the MERN stack, including MongoDB as the database, Express.js and Node.js for backend development, and React.js for the frontend interface. The main features include user registration and authentication, psychologist search based on categories, online consultation booking, Midtrans payment gateway integration, educational mental health articles, user profile management, comment and rating features, and an administrative dashboard for managing doctors, schedules, categories, articles, and orders. System validation was conducted using black-box testing across several browsers, including Google Chrome, Brave, and Microsoft Edge. The results indicate that all core functionalities operated successfully and responsively on both user and admin interfaces. This study contributes to the development of digital health information systems by providing an integrated web-based platform that improves accessibility, efficiency, and structured management of psychological consultation services. The originality of this study lies in the integration of mental health reservation services, category-based psychologist search, online payment, educational content, and administrative management within a single web-based system.